On the optical properties of monoclinic Na3AlF6 and Na3AlF6:Mn4+ - Thomas Jansen; David Böhnisch; Florian Baur; Thomas Jüstel (Optical Materials: X, 2023)
Mn4+ activated luminescent materials have attracted much attention as colour converters for light sources and displays. In particular, alkali metal hexafluorometallates, such as K2SiF6:Mn4+ or K2TiF6:Mn4+, emit light in the red spectral region if pumped by phosphor converted LEDs (pcLED). In accordance with Zhu et al. we applied the cation-exchange method in order to synthesize Mn4+ doped Na3AlF6. Na3AlF6:Mn4+ exhibits efficient red photoluminescence peaking at 627 nm, which can be assigned to the 2Eg → 4A2g intraconfigurational transition of Mn4+ ([Ar]3d.3 configuration) within the [MnF6]2- octahedra on the aluminum site in the cryolite host structure. Photoluminescence properties, such as temperature dependence of the PL intensity and luminescence lifetime are presented. Additionally, the band structure of the undoped host material has been treated with Density Functional Theory (DFT). The theoretical results have been evaluated experimentally with diffuse UV reflectance spectroscopy. Finally, luminous efficacy and color rendering values of simulated warm white emitting pcLEDs comprising a dichromatic phosphor blend employing Na3AlF6:Mn4+ as the red emitting component are calculated and compared to the performance of warm white emitting pcLEDs comprising K2SiF6:Mn4+ as red emitting component.